Phenotypic plasticity of vascular smooth muscle cells in vascular calcification: Role of mitochondria - Liu, Yan Zhong; Li, Zong Xiang; Zhang, Lin Lin; Wang, Dan; Liu, Yi Ping (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification (VC) is an important hallmark of cardiovascular disease, the osteo-/chondrocyte phenotype differentiation of VSMCs is the main cause of vascular calcification. Accumulating evidence shows that mitochondrial dysfunction may ultimately be more detrimental in the VSMCs calcification. Mitochondrial participate in essential cellular functions, including energy production, metabolism, redox homeostasis regulation, intracellular calcium homeostasis, apoptosis, and signal transduction. Mitochondrial dysfunction under pathological conditions results in mitochondrial reactive oxygen species (ROS) generation and metabolic disorders, which further lead to abnormal phenotypic differentiation of vascular smooth muscle cells (VSMCs). In this review, we summarize existing studies targeting mitochondria as a treatment for VC, and focus on VSMCs, highlighting recent progress in determining the roles of mitochondrial processes in regulating the phenotype transition of VSMCs, including mitochondrial biogenesis, mitochondrial dynamics, mitophagy, mitochondrial energy metabolism, and mitochondria/ER interactions. Along these lines, the impact of mitochondrial homeostasis on VC is discussed.